The Influence of Social Literacy on Students' Emotional Intelligence in Secondary Schools - Anisa Rahmawati (LP3M KH Yazid Karimullah Institute, 2025)
Emotional intelligence is an important factor in supporting student success both academically and socially. Social literacy, as the ability to understand and respond to social dynamics in the surrounding environment, is believed to have a major contribution to the development of emotional intelligence. This study aims to analyze the relationship between the level of social literacy and emotional intelligence of high school students. The method used is quantitative correlational with a sample of 120 students from three high schools in Yogyakarta. The data collection instrument was a Likert scale questionnaire measuring two main variables: social literacy and emotional intelligence. The results of statistical analysis showed a significant positive correlation between social literacy and emotional intelligence (r = 0.63; p < 0.01). This finding confirms that students with high social literacy skills tend to have better empathy, emotional regulation, and social skills. The implications of this study emphasize the importance of integrating character education and social literacy in the school curriculum as an effort to improve the quality of holistic and humanistic education.